Moods of overcoming communicative difficulties of the speaker in dialogue - Lebedevich, Roksana V. (Journal of the Belarusian State University. Philology, 2019)
The article analyzes the features of speech behavior of the dialogue participants in the situation of the origin and verbalization of the communicative difficulty of the speaker. The main directions of dialogue development in such cases are highlighted: ignoring the problem (at the initiative of the addresser or addressee) and attempting to overcome it (by the speaker himself or with the participation of the listener). The most common ways of overcoming such difficulties are considered. Factors influencing the choice of this or that way of overcoming the communicative difficulty of the speaker are determined.
Keywords: communicative difficulty; dialogue interaction; speaker; listener; ignoring the communicative difficulty; overcoming communicative difficulty; tactics to overcome communicative difficulties